From image schemata to rational inference structures and patterns - Godwins, Jude (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
When all is said and done, our power of abstract reason, under the framework proposed by proponents of imaginative reason, and reinforced by a host of thinkers sympathetic to their views, could well be identified with the human conceptualizing capacity. This has been found to involve three factors. The first factor is the power to create symbolic constructs corresponding to preconceptual structures in our commonplace experience. The second factor is the power of metaphorical mapping, framing structures in the physical sphere onto constructs in the abstract realms – all within the framework of the existing structural correspondences between the abstract and the physical horizons. The third factor is the power to employ image schemata as structuring schemes in the creation of general categories and complex concepts. If we should go by these schematic conceptualizations, meaning, understanding, and rationality would apparently be dependent on metaphorical extensions of non-propositional image-schematic structures.